2022
DOI: 10.1021/acsami.2c16702
|View full text |Cite
|
Sign up to set email alerts
|

Amide Linkages in Pyrene-Based Covalent Organic Frameworks toward Efficient Photocatalytic Reduction of Uranyl

Abstract: The bond linkages in covalent organic frameworks (COFs) partly determine its physical and chemical properties, thus affecting the photoreactive activity by influencing the generation of photoelectrons and the separation of excitons. Herein, pyrenebased amide COF 4,4′,4″,4‴-(pyrene-1,3,6,8-tetrayl)tetrabenzaldehyde−3,8-diamino-6-phenylphenanthridine (TFPPy−DP) was synthesized by postsynthetic modification of imine COFs. Due to the introduction of oxygen atoms into the framework and the change in polarity, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The amide COFs have large bandgaps and more negative CBs, which is beneficial for U(VI) photoreduction. The electron paramagnetic resonance analysis showed that single electrons were the main active species for U(VI) reduction, which was further evidenced by the intramolecular charge transfer calculation 51 …”
Section: Photocatalysismentioning
confidence: 76%
“…The amide COFs have large bandgaps and more negative CBs, which is beneficial for U(VI) photoreduction. The electron paramagnetic resonance analysis showed that single electrons were the main active species for U(VI) reduction, which was further evidenced by the intramolecular charge transfer calculation 51 …”
Section: Photocatalysismentioning
confidence: 76%
“…(f) Effect of pH on the removal of U for amide COFs, [U­(VI)] = 238 ppm and [ascorbic acid] = 0.5%. Reproduced with permission from ref . Copyright 2022, American Chemical Society.…”
Section: Uranium Enrichment and Separation From Wastewatermentioning
confidence: 99%
“…(g) EPR spectra of imine or amide COFs TFPPY-DP in aqueous solution at 10 min light irradiation, trapping agent: TEMPO. Reproduced with permission from ref . Copyright 2022, American Chemical Society.…”
Section: Uranium Enrichment and Separation From Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the perspective of green chemistry, if this method needs further development, some of the shortcomings need to be solved. First, as far as we all know, toxic reaction solvents such as 1,4-dioxane, mesitylene, N , N -dimethyl­formamide, dichlorobenzene, or the mixture of these solvent are commonly used reaction solvents in the solvothermal synthesis method. These solvents have typical characteristics of high toxicity and high pollution. Thus, green, low toxic, or even nontoxic solvents need to be developed to replace these organic solvents.…”
Section: Introductionmentioning
confidence: 99%